Organic Farming in the Tropical, Disaster-Prone Coasts: Interventions, Major Challenges and a Success Story from Sundarban Biosphere Reserve, India. Issue 1 (1st October 2022) - Chowdhury, A; Iyer, A S; Bhattacharyya, S; Khan, S U; Naz, A
Abstract: Organic agricultural practices are sustainable alternatives to chemical methods. This article highlights the major challenges faced by environmentalists, social workers in popularizing organic agriculture as well as its positive field application. The primary soil parameters (pH, alkalinity, electrical conductivity, soil, organic carbon, soil texture, and available N, P and K) are compared between global coastal agricultural soils. Organic farming practices adopted in different regions were also focused in this article. Sundarbans is the world's largest contiguous mangrove ecosystem, largest delta, abode of mangrove dwelling tigers and Indian part is the home of 4.6 million natural disaster vulnerable populations. This work showcases success story of organic farming by 84 families of Indian Sundarbans since 2012, with use of vermicompost, biopesticides (neem oil) and natural microbe augmentations ( Trichoderma sp ), as a part of a socio-environmental intervention project. This intervention resulted in increased yield in both kharif season (10-12%) and rabi season (5-10%) by 2017.